Effect of cutting fluid and spindle speed on surface hardness in turning AISI 4140 steel - Iswanto, Iswanto; Tjahjanti, Prantasi; Widodo, Edi; Chilmi, Muchammad (Universitas Muhammadiyah Metro, 2020)
This paper will discuss how the influence of different cutting fluid on surface hardness, how different spindle speed affect surface hardness, and are there interactions between cutting fluid and spindle speed on surface hardness of workpieces produced by conventional lathe. In this study, the variables that are varied are the cutting fluid and spindle speed. The cutting fluid used is: dromus, used oil SAE 40 and used cooking oil. While the spindle speed used is 370 rpm, 665 rpm, and 1040 rpm. Then the hardness of the workpiece surface is tested from the lathe process by varying the cutting fluid and the spindle speed. From the results of the hardness test on the surface of the workpiece, it can be concluded that: the greatest value of the surface hardness of the workpiece is obtained in the lathe process using dromus cutting fluid and the spindle speed used is 665 rpm. Whereas the smallest workpiece surface hardness value is obtained when using dromus cutting fluid using spindle speed of 1040 rpm. Cutting Fluid and Spindle Speed has a significant effect on surface hardness in the turning process of AISI 4140 steel